From Remote Work to Telework from Home: Occupational Health and Safety of White-Collar Employees - Ayşıl Kabakçı; Mehmet Güler (Sosyal Siyaset Konferansları Dergisi)
This study evaluates the method of teleworking from home from the perspective of white-collar workers, who are the most frequent users of this method and the most employed type of labor in the knowledge economy. The method of teleworking from home brings many benefits and risks from the perspective of white-collar workers. When examining the studies in the literature, factors have been determined to exist that are considered both benefits and risks in telework from home. One of these factors is occupational health and safety. In this context, evaluating occupational health and safety is of great importance. The implementation of occupational health and safety measures within the scope of teleworking from home reveals the significance of sharing legal responsibility and inconsistencies in practices regarding cases that have been brought to court. An examination of the studies in the literature shows the risks and dangers of teleworking from home in terms of occupational health and safety and the problems experienced in the process of taking precautions to be increasing daily. The aim of the study is to present arguments to support the idea that teleworking from home is more of a risk than a benefit in terms of occupational health and safety.